Homeschooled Students’ Motivations for Learning English as a Foreign Language: A Qualitative Study - Irma Amy Picauly; Natalia Christy Emy Lokollo; Listyani Listyani (Kelola: Jurnal Manajemen Pendidikan, 2023)
Homeschooling is an educational system that is different from the usual school system. From the name, homeschooling means an educational system that is done at home. In other words, homeschooling is family-based education. The levels of education covered in homeschooling can range from primary to secondary education. This study deals with twelve (12) teenage students’ motivations for learning English in a homeschool in Salatiga, Central Java, Indonesia. The participants aged between 12 and 13 years old. Data were collected through questionnaires and interviews with the students. Findings revealed that the twelve students had both intrinsic and extrinsic motivations in learning English. This study is hopefully beneficial for teachers teaching students in homeschools so that they can understand more deeply their students’ motivations in learning English. Also, it is hoped that EFL teachers teaching homeschooled students can motivate their students to have stronger motivations in learning this international language.